Agreement of Minimum Data Set 3.0 depression and behavioral symptoms with clinical diagnosis in a nursing home. (3rd October 2021) - Wei, Yu-Jung Jenny; Solberg, Laurence; Chen, Cheng; Fillingim, Roger B.; Pahor, Marco; DeKosky, Steven; Winterstein, Almut G
Abstract: Objectives: While the Minimum Data Set (MDS) 3.0 has adopted Patient Health Questionnaire (PHQ)-9 to screen for depression and rephrased language for behavioral symptoms among nursing home residents, it remains unclear how well the assessment data agree with medical records. Design: Using a retrospective review of MDS 3.0 linked to medical records between October 2010 and November 2017, we included residents with at least one quarterly or short-term (day 30 or day 60) MDS 3.0 assessment of depression PHQ-9 ( n  = 446) or behavioral symptoms ( n  = 460). For each resident of each cohort, we randomly selected an eligible MDS 3.0 depression and behavioral symptom assessment and compared against the respective medical diagnoses recorded within 30 days before the MDS 3.0 assessment. Results: Percent agreement was high for depression (90.1%) and behavioral symptoms (89.3%). Negative agreement was high for depression (94.8%) and behavioral symptoms (94.3%), while positive agreement was low for both conditions (4.3% and 10.9%). Conclusion: MDS 3.0 depression and behavioral symptoms had high overall and negative agreement, but low positive agreement with clinician diagnoses. MDS 3.0 data may be useful in ruling out depression and behavioral symptoms. Confirmation of the findings in a representative sample of nursing homes is warranted.